Ethnobotanical study of medicinal plants used for treatment of Diabetes in Southern Punjab, Pakistan - Sameen, Asifa; Sadia, Haleema; Sultana, Tahira; Khan, Khushdil; Malik, Khafsa; Shah, Hussain; Ullah, Ateef; U Din, Zohaib; Gul, Huma; Abdullah, Muhammad; Ahmad, Shabir (Ethnobotany Research and Applications, 2025)
Background: Diabetics is a chronic metabolic disease and a leading cause of death worldwide. In rural areas of Pakistan like Mianwali, diabetes management relies on medicinal plants due to limited access to healthcare and the high cost of treatments. This study highlights the potential of Indigenous medicinal plants as safer, cost-effective alternatives and supports for further research to identify active compounds for diabetes treatment. Methods: During October 2022 to December 2024 data was collected from 250 informants in Mianwali district through open interviews, semi-structured questionnaires and field surveys. Special focus was given to elderly respondents and traditional herbalists for their extensive knowledge of ethnomedicinal practices. The information was analyzed using the Use Value (UV), Family Importance Value (FIV), Relative Frequency Citation (RFC), and other quantitative indices. Results: The study identified 44 plant species from 25 families as medicinally significant for diabetes management. Herbs accounted for 48.83% of the recorded species, followed by trees (30.23%), shrubs (18.60%), and climbers (2.32%). Key families included Fabaceae, Cucurbitaceae, and Solanaceae. Quantitative indices revealed Moringa oleifera with the highest Use Value (UV = 0.97) and Rhazya stricta with the highest Fidelity Level (FL = 92.86%). Conclusions: This study highlights the rich ethnobotanical knowledge in the Mianwali district, documenting 44 plant species from 25 families used for diabetes management. Herbs were the most commonly utilized growth form (48.83%), reflecting their availability and versatility in treating various ailments. Keywords: Ethnobotany; Asteraceae, Indigenous knowledge; Used value, Herbal medicine, Mianwali, Diabetes, Cucurbitaceae